INTEGRASI PEMBAYARAN DIGITAL DALAM SISTEM AKUNTANSI BERBASIS CLOUD PADA STARTUP TEKNOLOGI MOKA POS DI INDONESIA - Puspita Romadhona; Wiwit Rohaeni Yulianti; Satria Chandra; Hartanti (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the impact of integrating digital payment systems with cloud-based accounting systems on financial management efficiency in Indonesian tech startups, using Moka POS as a case study. Employing a qualitative descriptive approach and secondary data analysis from company reports, the study finds that such integration enables automatic and real-time transaction recording, reducing dependence on manual processes prone to error. The results indicate improved operational efficiency, faster transaction reconciliation, and greater accuracy in financial reporting. These findings are supported by the national trend of significant growth in digital transactions during the 2020–2024 period. The study recommends enhancing digital literacy, developing user-oriented system features, and increasing policy support from the government to expand the sustainable adoption of such technology.